Collisional Quantum Dynamics for MgH− (1Σ+) With He as a Buffer Gas: Ionic State-Changing Reactions in Cold Traps - González-Sánchez, Lola; Gómez-Carrasco, Susana; Santadaría, Alberto M.; Wester, Roland; Gianturco, Francesco A. (Frontiers in Chemistry, 2019)
We present in this paper a detailed theoretical and computational analysis of the quantum inelastic dynamics involving the lower rotational levels of the MgH− (X1Σ+) molecular anion in collision with He atoms which provide the buffer gas in a cold trap. The interaction potential between the molecular partner and the He (1S) gaseous atoms is obtained from accurate quantum chemical calculations at the post-Hartree-Fock level as described in this paper. The spatial features and the interaction strength of the present potential energy surface (PES) are analyzed in detail and in comparison with similar, earlier results involving the MgH+ (1Σ) cation interacting with He atoms. The quantum, multichannel dynamics is then carried out using the newly obtained PES and the final inelastic rats constants, over the range of temperatures which are expected to be present in a cold ion trap experiment, are obtained to generate the multichannel kinetics of population changes observed for the molecular ion during the collisional cooling process. The rotational populations finally achieved at specific temperatures are linked to state-selective laser photo-detachment experiments to be carried out in our laboratory.All intermediate steps of the quantum modeling are also compared with the behavior of the corresponding MgH+ cation in the trap and the marked differences which exist between the collisional dynamics of the two systems are dicussed and explained. The feasibility of the present anion to be involved in state-selective photo-detachment experiments is fully analyzed and suggestions are made for the best performing conditions to be selected during trap experiments.